1987
DOI: 10.1002/pc.750080505
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic mechanical analysis studies of the interphase

Abstract: The dynamic mechanical properties of unidirectional glass‐fiber‐reinforced polyester measured along the fiber direction were recently investigated. In the same polyester, the type of organosilane coated on the glass fiber, the amount of organosilane, the fiber volume fraction, and the fiber diameter affect the value of the loss tangent, tan δ, at the glass‐transition temperature of the glass‐fiber‐reinforced polyester. The interfacial shear strength and the tan δ at the glass‐transition temperature of the glas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
62
0
2

Year Published

1998
1998
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 141 publications
(68 citation statements)
references
References 5 publications
4
62
0
2
Order By: Relevance
“…By way of a first approximation, the assumption is made that the mechanical loss factor tan d of the composite (tan d c ) can be expressed as follows 12,13 :…”
Section: / 8e20$$4955mentioning
confidence: 99%
“…By way of a first approximation, the assumption is made that the mechanical loss factor tan d of the composite (tan d c ) can be expressed as follows 12,13 :…”
Section: / 8e20$$4955mentioning
confidence: 99%
“…In a composite system, the presence of a filler affects the damping, due to shear stress concentrations. It is possible to correlate the changes in interfacial bonding to those in tan d intensity: the higher the damping at the interfaces, the poorer the interface adhesion, since a composite with poor interface bonding tends to dissipate more energy than that with good interface bonding [25]. The width of tan d peak is indicative of the volume of the interface, whereas eventual shifts in peak position could be ascribed to a lower or higher energy level required for the macromolecules motion and could be influenced by stress field surrounding the nanoparticles.…”
mentioning
confidence: 99%
“…The extent of the improvement observed in E 0 at the temperatures below and above the glass transition strongly depends on the preparation technique adopted. In the frame of this work, the same type of filler was used at the same content, therefore these changes could be likely due to the degree of GO dispersion/exfoliation which has a dramatic influence on the aspect ratio and, as a consequence, on the amount of the interphase regions (A/V) [25,27]. Indeed, the extent of the interface surface, i.e.…”
mentioning
confidence: 99%
“…For example, Chua [8] investigated the effects of organo-silane coatings on glass fibres and found that there was an inverse linear relationship between the intensity of the tan δ peak at the glass transition and the interfacial shear strength of glass/polyester composites measured by the shortbeam shear test (ASTM D2344).…”
Section: Dynamic Mechanical Analysismentioning
confidence: 99%
“…Results of using the DMA technique to characterise interfacial effects in particulate and fibre-reinforced polymer composites have been reported in the literature [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24]. Most of the studies were carried out in temperature sweeps at fixed frequencies (isochronal conditions) near transition regions of the matrix, specially covering the glass transition region.…”
Section: Introductionmentioning
confidence: 99%